2017
DOI: 10.1111/aor.12882
|View full text |Cite
|
Sign up to set email alerts
|

Training Improves Vibrotactile Spatial Acuity and Intensity Discrimination on the Lower Back Using Coin Motors

Abstract: Tactile vision substitution devices are assistive technologies for the blind that redirect visual information to the tactile sense. They typically include a tactile display that conveys visual information to the skin. Two important parameters that determine the maximum information bandwidth of tactile displays are the spatial acuity of the skin, and the ability of the user to discriminate between stimulus intensities. These two parameters were investigated by determining the two-point discrimination (TPD) thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…We used commercially available 10 mm coin disc tactors (Precision Micro-drives Inc., London, Model 310-117). These inexpensive devices are energy-efficient, easy to use (Stronks et al 2015;Stronks et al 2017), and have been successfully used for similar purposes in recent works (Krueger et al 2017;Shah et al 2018). Vibration is produced by an eccentric rotating mass, the speed of which is controlled by an applied voltage within the range 0V to 3V.…”
Section: Experimental Setup and Protocolmentioning
confidence: 99%
“…We used commercially available 10 mm coin disc tactors (Precision Micro-drives Inc., London, Model 310-117). These inexpensive devices are energy-efficient, easy to use (Stronks et al 2015;Stronks et al 2017), and have been successfully used for similar purposes in recent works (Krueger et al 2017;Shah et al 2018). Vibration is produced by an eccentric rotating mass, the speed of which is controlled by an applied voltage within the range 0V to 3V.…”
Section: Experimental Setup and Protocolmentioning
confidence: 99%
“…Our subjects were all naïve to the tasks and they did not receive any training. Previous experiments have shown significant training effects in a vibrotactile acuity task using the same motors and we expect that the performance on the grating task with our prototype vibrotactile display may improve likewise. We deliberately did not train our subjects because of the relatively small number of possible grating stimuli that can be generated with an 8 by 8 display.…”
Section: Discussionmentioning
confidence: 73%
“…Stronks et al of the NICTA, Computer Vision Research Group, Canberra, Australia investigated the spatial acuity of the skin and the ability of the user to discriminate between stimulus intensities in tactile vision substitution devices for the blind using coin motors on the lower back. It was found that 10 min of computer‐assisted training improved the vibrotactile two‐point discrimination threshold on the lower back by 36%, and that 18 min of training improved the just‐noticeable intensity difference by 44%.…”
Section: Visual Supportmentioning
confidence: 99%